Sa ngalan ng ina sandaang taon ng tulang feminista sa Pilipinas, 1889-1989 - Santiago, Lilia Quindoza 1949- (Quezon City University of the Philippines Press, 1997)
Feminism in the Philippines.
UCWS-2014-G-1901 donated by U.P. Press.
Keywords: Women in literature; Tagalog poetry; Tagalog poetry -- History and criticism; Philippine poetry (English); Feminism -- Philippines -- Poetry